Malaysian Students' Interests In Learning Science And Technological Topics. - Suan, Yoong; Ayob, Aminah (2004)
Falling recruitment and interests in Science and Technological (S&T) studies and careers has been observed in many countries, The lack of relevance of the S&T curriculum has been identified as one of the greatest barriers for good learning as well as stimulating interests in the subject.